PENGGUNAAN KECERDASAN BUATAN UNTUK PERSONALISASI PENGALAMAN BELAJAR - Arnadi Arnadi; Aslan Aslan; Arnes Yuli Vandika (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
Using Artificial Intelligence (AI) to Personalise Learning Experiences refers to the application of AI technology and machine learning algorithms in an educational context to create individually tailored learning experiences for each learner. This approach leverages AI's ability to analyse big data about each student's learning paterns, strengths, weaknesses and preferences, then uses that information to adjust content, pace and teaching methods in real-time. The aim is to optimise the learning process by providing the most relevant and effective material for each individual. In practice, these AI-based systems can recommend appropriate learning resources, adjust task difficulty levels, provide personalised feedback, and even predict areas where a student may struggle in the future. This approach not only includes customisation of academic content, but can also take into account factors such as a student's learning style, motivation, and socio-emotional context. Thus, the use of AI to personalise learning experiences aims to create an educational environment that is more inclusive, effective, and responsive to the individual needs of each learner.